Impacto ecológico em Tucuruí (PA): Climatologia - Fisch, Gilberto F.; Januário, Mauro; Senna, Renato C. (Acta Amazonica, 1990)
In this work, the climatic pattenn of the UHE Tucuruí - Regiοn is shown, for the period of december/1982 to december/1986. The seasonal patterns of temperature, relative humidity, wind velocity (2 m height) precipitation, intensity of solar radiation and the ratio of sunshine hours are presented. Penman-Monteith's method is used to determine the potential evapotrasnpiration if that region. As a result daily evapotranspiration avenage is higher than in the literature, because assumed the saturation of the surface for all months that antecipate the formation of the reservoir.", 'en